(untitled) (Integral Research, 2024)
This paper examines Sri Aurobindo’s philosophy of moral ethical development and its significance for education. Aurobindo’s model, unlike most traditional approaches, embodies all three areas of growth—spiritual, intellectual, and emotional—allowing for inward self-discovery as the substructure for outward moral action. This study explores his view of the human soul, the psychic being, and the significance of education to awaken the moral consciousness. The study compares Aurobindo’s model with contemporary functionalist models of moral education, and offers ways to translate Aurobindo’s vision in practice, by proposing a much more coherent and integral moral education model for both the student and the teacher.